Power after carbon building a clean, resilient grid - Fox-Penner, Peter S., 1955- (Harvard University Press, 2020)
"As the damaging and costly impacts of climate change increase, the rapid development of sustainable energy has taken on great urgency. The electricity industry has responded with necessary but wrenching shifts toward renewables, even as it faces unprecedented challenges and disruption brought on by new technologies, new competitors, and policy changes. The result is a collision course between a grid that must provide abundant, secure, flexible, and affordable power, and an industry facing enormous demands for rapid, systemic change and power. The fashionable solution is to think small: smart buildings, small-scale renewables, and locally distributed green energy. But Peter Fox-Penner makes clear that these will not be enough to meet our increasing needs for electricity. He points instead to the indispensability of large power systems, battery storage, and scalable carbon-free power technologies, along with the grids and markets that will integrate them. The electric power industry and its regulators will have to provide all of these, even as they grapple with changing business models for local electric utilities, political instability, and technological change. Power after Carbon makes sense of all the moving parts, providing actionable recommendations for anyone involved with or relying on the electric power system"--